Patterns of Tobacco-Use Behavior Among Chinese Smokers with Medical Conditions - Wong, Candice C. (Springer US, 2009)
Understanding the characteristics of Chinese American smokers with medical conditions and factors associated with their tobacco-use behaviors will guide effective cessation programs. In 2008, the authors described socio-demographic profiles of Chinese smokers with medical conditions treated during the period 2002–2006, documented their tobacco-use behaviors (i.e., average daily cigarette use, nicotine dependence, and number of past-year quit attempts), and drew comparisons between subjects recruited from hospitals (IP) and ambulatory settings (OP). Compared to OP, IP were significantly older, less educated, less acculturated, and more likely to be retired. Of the two groups, IP had poorer disease profiles, smoked less (4.4 vs. 11.9 cigarettes per day), and had lower nicotine-addiction scores (5.5 vs. 6.7). There was no difference between groups in past-year quit attempts. After adjustments, the data revealed that being employed and OP was associated with higher average daily cigarette use; IP were less nicotine dependent than OP; and for both groups, years of smoking was negatively associated with past-year quit attempts. Our study suggests that, more than acculturation level, health status influences the Chinese smoker’s level of cigarette use and nicotine addiction. Given the severity of their disease profiles, IP should be aggressively targeted for intervention, as they are more likely to be light smokers and to be less nicotine dependent than OP. Future tobacco treatment studies should pay attention to health status among smokers in health-care settings in order to provide a more accurate assessment of treatment needs and of barriers to successful smoking cessation.